Seroepidemiology of hepatitis A and B and vaccination status in staff at German schools for the handicapped. Issue 5 (14th October 2016) - Claus, Matthias; Kimbel, Renate; Schöne, Klaus; Letzel, Stephan; Rose, Dirk‐Matthias
Abstract : This study aims to assess serostatus and vaccination status of hepatitis A and B among staff at schools for the handicapped. We also wanted to investigate factors associated with serostatus, number of infections with hepatitis A/hepatitis B at work, and factors influencing being vaccinated or not. The cross‐sectional study was carried out between August 2010 and August 2012 at 13 German schools for severely handicapped. Data were analyzed using blood samples, vaccination documents, and questionnaires. A total of 395 persons participated in our study (response: 59.7%), information on 367 could be used for analysis. Two respondents have been infected with HAV at work, 53.4% were anti‐HAV seropositive. Vaccination against hepatitis A was influenced by information about infectious diseases before starting to work, level of education, and marital status. One person got infected with hepatitis B during work, 53.2% were anti‐HBs‐seropositive. Vaccination against hepatitis B depended on perceived burden by nursing activities, and vaccination costs being paid by employer. Immunity to hepatitis A and B in our sample is insufficient and does not correspond to the infectious risks. Two persons got infected with hepatitis A and one person with hepatitis B during work at school, indicating an urgent need for preventive actions. J. Med. Virol. 89:825–833, 2017 . © 2016 Wiley Periodicals, Inc.